STRATEGI SUKSES PERAN PERPUSAKAAN UMUM DALAM MENDUKUNG TERCAPAINYA SDG’S UNTUK MASYARAKAT SEJAHTERA - Safira, Fidan; Putra, Dedy Dwi (Journal of Documentation and Information Science, 2019)
Sustainable development goals is an effort to bring universal vision in order welfare society and the sustainability of life. To help deliver that agenda, the library turned out to be the also contribute in it. Through a narrative qualitative approach, this study will explain the role of Indonesia?s public library in order to support sustainable development goals. The result of this research showed that library an important role in support welfare society and sustainable development goals. As a dynamic organization, library capable to accommodate of information needs from various aspect such as good health, environment, political and economic. Library able to provide access to information support the policy, providing a place for community engagement, build a network with various parties, and mentoring to know impact of library services.